PENGELOLAAN BERITA PADA MAJALAH COMMAGZ DENGAN MEMBANGUN E-MAGAZINE - JENIE SUNDARI (LPPM Universitas Bina Sarana Informatika, 2015)
Website or commonly referred to as Web is an internet resource. By using the website, the communication will run quickly, easily and inexpensively. So it is not surprising that every company has a website that is used to introduce the company and its products. In the promotion of products of PT Global Development Unggul still use the print media and electronic media. By using these two media promotion expenses to be expensive and inefficient because companies will expend not less. The authors took the initiative to design web Unggul PT Global Development Using the web, the information will be readily available, easily updated information and cost. Data collection methods that I use is the interview, study the literature and observations directly to the field. Management of e-magazine was created using the software development method waterfall, and modeling tools using UML (Unified Modeling Language)